SUPPORTING RURAL ENTREPRENEURSHIP BY RDP 2007–2013 - Babuchowska, Karolina; Marks-Bielska, Renata (Acta Scientiarum Polonorum. Oeconomia, 2010)
The aim of the study was to show implementation of the measure ‘Creating and development of microenterprises’ in Warmia and Mazury province. Information for the study was provided by regional branch of the Agency for Restructuring and Modernization of Agriculture. In Warmia and Mazury province the largest initiative in development of micro-enterprises is characteristic for the inhabitants of districts located in central part of the region. Project costs, planned in the applications, show wide variations, with domination (27.81%) of the applications in which the total estimated cost of planned investments stays in the range of 200 000–299 999 PLN.